Duration of labor with meperidine versus placebo in singleton term pregnancies: A randomized placebo controlled study - Şahin, Orhan; Genç, Simten; Çetinkaya, Nur; Mihmanlı, Veli; Yıldırım, Gökhan; Tekirdağ, Ali İsmet (Galenos Publishing House, 2022)
Objective: Meperidine, a synthetic opioid analgesic, is used empirically in many birth centers due to its effect on the duration of labor as well as pain relief during labor. In this study, we examine the effect of meperidine administration on the duration of labor. Methods: This study was designed as a prospective randomized placebo-controlled study; 250 patients were randomized into two groups where the study group received 0.5 mL-25 mg i.v. meperidine and the control group received 0.5 mL i.v. saline solution, all at the start of the active phase. The start of the active phase of labor was defined as 4 cm cervical dilatation and 60%-70% cervical effacement. The primary outcome was determined as the duration of the active phase (DAP). This study is registered on ClinicalTrials.gov (identifier: NCT01555671). Results: Women randomized to the meperidine group had a shorter total duration of labor (TDL) and shorter duration of the DAP compared to the control group, both in the total patient population women (mean ± standard deviation (SD): 273±129 min vs. 331±177 min, p=0.033; 249±122 min vs. 304±167 min, p=0.029, respectively) and in primiparous (mean ± SD: 372±134 min vs. 400±179 min, p=0.026; 296±126 min vs. 363±170 min, p=0.024, respectively). No statistically significant difference was found between the total patient population and primiparous group in terms of the second stage of labor (DSS) (p=0.930, p=0.229; respectively). Multiparous women in meperidine and control groups, did not show a statistically significant difference in terms of the TDL, DAP and the DSS (p=0.170, p=0.157, p=0.498; respectively). No statistically significant difference was found between the two study groups in terms of age (p=0.126), parity (p=0.427), body mass index (p=0.163), cesarean rates (p=0.511) and mean gestational weeks (p=0.845). Conclusion: Our findings revealed that meperidine administration was associated with a shorter duration of active phase of labor in primiparous women.
Keywords: Active Phase; Apgar; Duration Labor; Labor Analgesia; Meperidine; Pethidin